High-Strength Al-Based Bulk Alloy Produced by Spark Plasma Sintering of Gas Atomized Powders - Nguyen, Hoang Viet (Old Journal, 2019)
In this work, consolidation of gas atomized Al84Gd6Ni7Co3 glassy powders into highly dense bulk specimens was carried out by spark plasma sintering. The highest relative density and hardness value can be obtained for sample sintered at 613 K are about 99.7 % and 495 HV, respectively. Room temperature compression tests of the consolidated bulk material reveal remarkable mechanical properties, namely, high compression strength of 1020 MPa with maximum elongation of 3.2 %, but without plastic deformation. The failure morphology of the sintered sample surface presented a transparticle fracture mechanism, indicating the efficiency of the sintering processing.